2012
DOI: 10.1249/mss.0b013e31823f6887
|View full text |Cite
|
Sign up to set email alerts
|

Conduit Diameter and Wall Remodeling in Elite Athletes and Spinal Cord Injury

Abstract: These findings suggest that remodeling of the arterial wall occurs systemically in response to exercise training and is unrelated to exercise type in humans. Conversely, localized effects are evident with respect to the effect of exercise on arterial diameter. These findings have implications for our understanding of the effects of exercise on arterial structure and function in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 31 publications
8
74
1
Order By: Relevance
“…In contrast, Rowley et al found a smaller carotid artery wall thickness in elite athletes compared to sedentary controls (261,262). One explanation for these differences in findings is that elite athletes are exposed to a larger volume, duration and intensity of exercise than recreationally active subjects (212,247,285).…”
Section: Conduit Arteries (Wall Thickness) When Directly Comparing Ementioning
confidence: 93%
See 2 more Smart Citations
“…In contrast, Rowley et al found a smaller carotid artery wall thickness in elite athletes compared to sedentary controls (261,262). One explanation for these differences in findings is that elite athletes are exposed to a larger volume, duration and intensity of exercise than recreationally active subjects (212,247,285).…”
Section: Conduit Arteries (Wall Thickness) When Directly Comparing Ementioning
confidence: 93%
“…rowing) versus cyclical (e.g. rhythmic handgrip) muscular contraction warrants further investigation (261,262).…”
Section: Green Et Al Exercise Hemodynamics and Vascular Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectional studies in healthy subjects demonstrated that athletes have a generally lower artery wall thickness compared to sedentary controls (Rowley et al 2012;Rowley et al 2011;Maiorana et al 2011). A recent study in healthy young men confirmed the presence of a generalised decrease in arterial wall thickness after 8-weeks cycling exercise training (3 sessions per week) on both the carotid and the superficial femoral artery (Thijssen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that the circulating levels of angiogenic factors in response to exercise also increased significantly in individuals with SCI; this implies that these factors are involved in exercise-induced vascular remodeling and angiogenesis in these individuals as well. [21][22][23][24][25] This study is the first to investigate the responses of angiogenic molecules to exercise in individuals with SCI; thus, comparisons with previous studies using this population are not possible. However, earlier work in humans with intact spinal cords supports our findings in AB.…”
Section: Discussionmentioning
confidence: 99%